2011
DOI: 10.4048/jbc.2011.14.4.289
|View full text |Cite
|
Sign up to set email alerts
|

Locoregional Recurrence of Breast Conserving Surgery after Preoperative Chemotherapy in Korean Women with Locally Advanced Breast Cancer

Abstract: PurposePreoperative chemotherapy has been used to increase the rate of breast conserving surgery (BCS) in Caucasian women. However, whether it would also increase the rate of BCS in Korean women has not been verified. The aim of this study was to determine the effectiveness of preoperative chemotherapy to make BCS possible in Korean women who have locally advanced cancer without any increase of locoregional recurrence according to operation methods (BCS vs. mastectomy).MethodsFrom August 2002 to April 2005, 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 27 publications
0
6
1
Order By: Relevance
“…Only a negligible number of our patients had breast conserving surgery (BCS). Early presentation and the availability and extensive use of adjuvant therapies have made BCS to gain widespread usage in some parts of the world [ 27 , 28 ]. This is especially so in developed countries where evidence now abounds that it is as effective as MRM in early breast cancer [ 2 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Only a negligible number of our patients had breast conserving surgery (BCS). Early presentation and the availability and extensive use of adjuvant therapies have made BCS to gain widespread usage in some parts of the world [ 27 , 28 ]. This is especially so in developed countries where evidence now abounds that it is as effective as MRM in early breast cancer [ 2 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…As many of the patients were also participants in various clinical trials of NAC that were being conducted at the National Cancer Centre, Korea, during this period, the NAC regimens were not uniform for all patients [ 15 , 16 ]. The regimens included four cycles of doxorubicin and cyclophosphamide, four cycles of doxorubicin and cyclophosphamide followed by four cycles of either docetaxel or paclitaxel, six cycles of doxorubicin and docetaxel, four cycles of paclitaxel and gemcitabine, and six cycles of paclitaxel, gemcitabine, and trastuzumab or lapatinib.…”
Section: Methodsmentioning
confidence: 99%
“…BCS rates reportedly increased overall after NAC [ 31 ]. In our study, we analyzed patients with and without cCR who received BCS and found that BCS was more likely to be successful in cCR patients.…”
Section: Discussionmentioning
confidence: 99%